Endothelium-specific amyloid precursor protein deficiency causes endothelial dysfunction in cerebral arteries - d’Uscio, Livius V (J Cereb Blood Flow Metab, 2017)
The exact physiological function of amyloid-β precursor protein (APP) in endothelial cells is unknown. Endothelium-specific APP-deficient (eAPP(−/−)) mice were created to gain new insights into the role of APP in the control of vascular endothelial function. Endothelium-dependent relaxations to acetylcholine were significantly impaired in basilar arteries of global APP knockout (APP(−/−)) and eAPP(−/−) mice (P < 0.05). In contrast, endothelium-independent relaxations to nitric oxide (NO)-donor diethylamine-NONOate were unchanged. Western blot analysis revealed that protein expression of endothelial nitric oxide synthase (eNOS) was significantly downregulated in large cerebral arteries of APP(−/−) mice and eAPP(−/−) mice as compared to respective wild-type littermates (P < 0.05). Furthermore, basal levels of cyclic guanosine monophosphate (cGMP) were also significantly reduced in large cerebral arteries of APP-deficient mice (P < 0.05). In contrast, protein expression of prostacyclin synthase as well as levels of cyclic adenosine monophosphate (cAMP) was not affected by genetic inactivation of APP in endothelial cells. By using siRNA to knockdown APP in cultured human brain microvascular endothelial cells we also found a significant downregulation of eNOS mRNA and protein expressions in APP-deficient endothelium (P < 0.05). These findings indicate that under physiological conditions, expression of APP in cerebral vascular endothelium plays an important protective function by maintaining constitutive expression of eNOS.